How can problem-based learning be realised in blended learning format? Contribution to the HoGe conference 2018 "Digital learning and teaching" / Wie kann problembasiertes Lernen im Blended-Learning-Format umgesetzt werden? Beitrag zur HoGe-Tagung 2018 "Digitales Lernen und Lehren" - D. Ammann; Y. Vignoli; S. Kaap-Fröhlich (Sciendo, 2019)
Students can prepare themselves for the growing demands in the eHealth sector by using media-supported teaching settings during their training. Problem-based learning (PBL) is a learner-centered educational approach based on authentic problems. The 7 Jump Method is an established method for the implementation of PBL and for the theoretical treatment of problems in class. PBL is subject to the danger of "understeering the learning process" (Müller Werder, 2013). E-learning can make process control more eficient and structure it beter through role-specific templates. Using the example of a course of study in nursing at the Höhere Fachschule in Switzerland, the first possibilities for implementation in the health care professions are pointed out and critically discussed. The present case study was intended to answer this question: How can problem-based learning be realised in blended format?